Long‐term outcomes following restorative proctocolectomy ileal pouch‐anal anastomosis in pediatric ulcerative colitis patients: Multicenter national study in Japan. Issue 6 (27th July 2018) - Ikeuchi, Hiroki; Uchino, Motoi; Sugita, Akira; Futami, Kitaro; Fukushima, Kouhei; Hata, Keisuke; Koganei, Kazutaka; Kusunoki, Masato; Uchida, Keiichi; Nezu, Riichiro; Kimura, Hideaki; Takahashi, Kenichi; et al.
Abstract: Background: Few studies have investigated surgical outcomes following a colectomy in pediatric patients with ulcerative colitis (UC). Purpose: This study aimed to determine long‐term outcomes in a large cohort of pediatric patients who underwent proctocolectomy with ileal pouch‐anal anastomosis (IPAA) for UC. Methods: Pediatric patients (<17 years old) who underwent surgery at 12 different hospitals in Japan between May 1979 and March 2015 were included in this study. Information was obtained by the use of a questionnaire survey. Results: There were 113 (53.3%) male and 99 (46.7%) female pediatric patients. The most common indication for elective surgery was failure of medical management, whereas emergency surgery was carried out for fulminant cases. A hand‐sewn IPAA was used with a mucosectomy in 112 (52.8%), stapled anastomosis in 93 (43.9%), and not specified in 7 (3.3%) patients. Small bowel obstruction and surgical site infection were the most frequent early postoperative complications (POC), whereas pouchitis, small bowel obstruction, and perianal fistula were frequent late POC. The most common late POC was pouchitis, found in 38 (17.9%) of the patients, whereas pouch failure was noted in 11 patients at the latest follow‐up examination. Cumulative pouch survival rate after 10 years was 91.7%. There were no significant differences regarding gender or anastomotic procedure in relation to cumulative pouch survival rate. Conclusion: To avoid pouch failure following an IPAA procedure, it is important to recognize that pouchitis or an anal fistula may lead to this condition in pediatric UC patients. Abstract : Cumulative pouch function rate was 93.2% in boys (red line) and 90.1% in girls (blue line) at 10 years after the operation, which was not significantly different ( P  = 0.35).